2018
DOI: 10.2147/cia.s155793
|View full text |Cite
|
Sign up to set email alerts
|

Is grand multiparity a risk factor for the development of postmenopausal osteoporosis?

Abstract: ObjectiveIn this study, we investigated the relationship between the development of postmenopausal osteoporosis and parity.Materials and methodsThe retrospective study included 129 postmenopausal women who were divided into three groups depending on the number of parity: Group I, <5; Group II, 5–9; and Group III, ≥10. The mean age of the subjects was 57.71±5.02 years.ResultsNo significant difference was found among the three groups regarding body mass index values, duration of menopause, mean thyroid stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…Demir and colleagues also showed that postmenopausal osteoporosis is associated with duration of menopause rather than age at menopause [32], and bone loss is accelerated mainly due to rapid estrogen deprivation. In parallel with some studies [33,34], we could not detect significant relation between multiparity and osteoporosis. At the same time, Peker et al showed a significant association between femoral osteoporosis and multiparity but not in lumbar osteoporosis [33].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Demir and colleagues also showed that postmenopausal osteoporosis is associated with duration of menopause rather than age at menopause [32], and bone loss is accelerated mainly due to rapid estrogen deprivation. In parallel with some studies [33,34], we could not detect significant relation between multiparity and osteoporosis. At the same time, Peker et al showed a significant association between femoral osteoporosis and multiparity but not in lumbar osteoporosis [33].…”
Section: Discussionsupporting
confidence: 83%
“…In parallel with some studies [33,34], we could not detect significant relation between multiparity and osteoporosis. At the same time, Peker et al showed a significant association between femoral osteoporosis and multiparity but not in lumbar osteoporosis [33]. Some other studies revealed a negative effect of multiparity on bone density [32,35].…”
Section: Discussionsupporting
confidence: 83%
“…However, a similar tendency of younger women having better screening practice than older women in Karachi was previously observed in a study carried out in 2018, which concluded that the most frequent age of diagnosis for breast cancer was in the 40s [24]. No significant association was detected between multiple pregnancies and better DEXA practice either, even though the frequency of osteoporosis in a study was found to be significantly higher in women with five to nine pregnancies compared with women having <5 pregnancies [25]. However, the link between parity and BMD and duration of breastfeeding and BMD remains largely unclear, as some reports have shown that bone loss associated with these factors is recovered after weaning [26].…”
Section: Discussionsupporting
confidence: 58%
“…In a hospital-based cross sectional study from India, parity was negatively correlated with the BMD of neck of the femur, trochanter, lumbar spine, and forearm [6]. In a study from Turkey, low BMD was associated with high parity in postmenopausal women [7]. Similar research demonstrated that low BMD of the spine and hip in postmenopausal women with parity greater than six [8].…”
Section: Discussionmentioning
confidence: 78%